Fundamentals of Corporate Finance (sách photo) - Brealey Richard A (McGraw Hill/Irwin, 2004)
Brealey, Myers, Marcus have been applauded for their intuitive approach and imbedded examples. Professors constantly praise their well-organized and thoughtful writing style and their clear exposition of what many students consider difficult material. The authors accomplish this without sacrificing an up-to-date, technically correct treatment of core topic areas. Since this author team is known for their outstanding research, teaching efforts, and market-leading finance textbooks, it’s no surprise that they have created an innovative modern, and market-driven revision